2013
DOI: 10.1590/s0103-21002013000600012
|View full text |Cite
|
Sign up to set email alerts
|

Sentimentos dos cuidadores de usuários de bebidas alcoólicas frente à internação

Abstract: Objective: To describe caregivers' feelings about alcohol abusers at hospital admission to the intensive care unit. Methods: This qualitative study included ten family caregivers of patients admitted to an intensive care unit with a diagnosis of chronic alcohol use. Data were collected by semi-structured interviews at the respondents' homes, and data were subsequently submitted to content analysis. Results: The caregivers reported suffering, sadness, desperation, and guilt. Religion appeared as a way to confro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
1
0
7
Order By: Relevance
“…Observa-se, conforme informações na tabela 1 de caracterização das publicações, na primeira década dos anos 2000, que sete artigos (18)(19)(20)(21)(22)(23)(24) acerca da temática foram publicados. Há maior predominância entre os anos de 2012, 2013 e 2014, totalizando 12 artigos (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) quando somados. Com relação à área mais frequente, a enfermagem se sobressai, com 19 artigos (19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) , o que é reforçado pela especifi cidade das revistas em que esses artigos foram publicados: Revista de Enfermagem Escola Anna Nery, com quatro artigos (33,35,(37)(38) , seguida da revista Ciência, Cuidado e Saúde da Faculdade de Enfermagem da Universidade Estadual de Maringá, com três artigos (22,(24)(25) e das revistas Texto e Contexto -Enfermagem ...…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Observa-se, conforme informações na tabela 1 de caracterização das publicações, na primeira década dos anos 2000, que sete artigos (18)(19)(20)(21)(22)(23)(24) acerca da temática foram publicados. Há maior predominância entre os anos de 2012, 2013 e 2014, totalizando 12 artigos (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) quando somados. Com relação à área mais frequente, a enfermagem se sobressai, com 19 artigos (19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) , o que é reforçado pela especifi cidade das revistas em que esses artigos foram publicados: Revista de Enfermagem Escola Anna Nery, com quatro artigos (33,35,(37)(38) , seguida da revista Ciência, Cuidado e Saúde da Faculdade de Enfermagem da Universidade Estadual de Maringá, com três artigos (22,(24)(25) e das revistas Texto e Contexto -Enfermagem ...…”
Section: Resultsunclassified
“…Há maior predominância entre os anos de 2012, 2013 e 2014, totalizando 12 artigos (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) quando somados. Com relação à área mais frequente, a enfermagem se sobressai, com 19 artigos (19)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) , o que é reforçado pela especifi cidade das revistas em que esses artigos foram publicados: Revista de Enfermagem Escola Anna Nery, com quatro artigos (33,35,(37)(38) , seguida da revista Ciência, Cuidado e Saúde da Faculdade de Enfermagem da Universidade Estadual de Maringá, com três artigos (22,(24)(25) e das revistas Texto e Contexto -Enfermagem (19,27) , Revista Eletrônica de Enfermagem (28,36) , Acta Paulista de Enfermagem (29) (30) e Revista Brasileira de Enfermagem (32)…”
Section: Resultsunclassified
See 1 more Smart Citation
“…The often reported applications for highly alloyed superaustenitic stainless steels, such as 654SMO, are high-temperature, high-chloride environments, which include desalination, [96] pulp and paper mills, [97] biomass combustion, [98] exhaust gas cleaning, [99] and geothermal wells, [100,101] among others. Taking into account the composition of cupric chloride leaching solutions used in the EDRR process (Table II) and its acidity (pH<2), it can be concluded that out of the investigated alternatives, the 654SMO steel is the adequate choice of the electrode material to be used in the scale-up of the EDRR process.…”
Section: Selection Of the Optimum Electrode Materialsmentioning
confidence: 99%
“…Neste setor, observa-se que as pessoas, ao visitarem seus familiares internados, demonstram muito receio e temem pela vida dos mesmos, ao vê-los frágeis e dependentes de muitos cuidados. A internação em UTI também pode ocasionar angústia ao cuidador familiar, pois além da possibilidade do tipo de cuidado prestado ao usuário de álcool, possivelmente, ser alterado após a internação nessa unidade, por motivo de sequelas físicas ou mentais, há também a possibilidade da morte deste familiar como desfecho da internação (8) .…”
Section: Introductionunclassified